The Analysis of Personal Protective Equipment Covid-19 in The Hospital Sallewangan, Maros Regency 2020 - Fetrawaty Mansyur (Indian Journal of Forensic Medicine & Toxicology, 2022)
Purpose: to analyze of the use of Covid-19 Personal Protective Equipment on health workers atSalewangang Hospital, Maros Regency.Methods: The type of research used is the analytical survey method of research conducted withoutintervention to the research subject. Data collection regarding free and dependent variables was carriedout online using Google Form and the results of Google Form data collectionResults: Availability of personal protective equipment has a significant effect on the behavior ofusing personal protective equipment Covid-19, Knowledge of health workers has a significant effecton behavior of using personal protective equipment Covid-19, Attitudes of health workers have asignificant effect on behavior of using personal protective equipment Covid-19 in health workers at theSalewangang Hospital, Maros Regency with a sig. 0.000Conclusion: there is a relation between personal equipment on helath workers at the sallewanganhospital at maros regency